Evidence for widespread occurrence of copper in Late Neolithic Poland? A deposit of Funnel Beaker Culture bone products at site 2 in Osłonki (Kuyavia, central Poland). (5th April 2018) - Osipowicz, Grzegorz; Kuriga, Justyna; Makowiecki, Daniel; Bosiak, Mariusz; Grygiel, Ryszard
Abstract: In the course of archaeological research at site 2 in Osłonki (Kuyavia, central Poland), a dense deposit of 20 cattle bones was discovered, most of which are semi-finished products for production of bone chisels. The collection was dated ab. 3350-3097 calBC. The traceological analysis of technological traces on the artefacts and experimental studies indicate that they were processed using several metal tools with working edges of varying shape, employed as chisels for bone splitting. Although SEM-EDX analyses did not show the presence of a substantial amount of copper on the surfaces of the artefacts, the collection can be considered most likely evidence for widespread use of this metal among Late Neolithic communities in Poland or at least the people who inhabited the area of Kuyavia.